Establishing Foundational Data on the Mental Health Functioning, Stress, Mood, Self-Regulation Capacity, and Perceptions of Coaching Climate of Canadian Interuniversity Sport (CIS) Student-Athletes - Van Slingerland, Krista (Université d'Ottawa / University of Ottawa, 2016)
Mental health has become increasingly important on post-secondary campuses across Canada, as the majority of university students represent the cohort of the Canadian populace that is most vulnerable to mental illness, substance abuse, and suicide. Evidence suggests that student-athletes, a visible and diverse sub-population of university students, are at equal risk of experiencing a mental illness (Reardon & Factor, 2010), but could be even more vulnerable to mental health challenges than their non-athlete peers (Neal et al., 2013; Watson & Kissinger, 2007), given the additional demands and pressures that they face. Problematic though, is that the culture of athletics and prevailing stigma surrounding mental illness can lead student-athletes to overreport their well-being and deny distress (Steiner, Denny, & Stemmle, 2010), as well as underutilize the mental health services available to them on campus (Lopez & Levy, 2013). Although researchers have investigated the mental health of American college students (e.g., Eklund, Dowdy, Jones, & Furlong, 2011) and attempted to understand the vulnerability of National Collegiate Athletics Association (NCAA) student-athletes to specific mental illnesses (e.g., eating disorders and substance abuse, Reardon & Factor, 2010), no study to date has investigated the mental health of student-athletes competing in Canadian Interuniversity Sport (CIS), particularly not using a holistic lense. As such, the overall purpose of the present study was to provide foundational data relating to Canadian student-athletes’ mental health functioning and other relevant indices such as their stress levels, mood, capacity to self-regulate, and perceptions of coaching climate. The first objective was to understand (a) the level and prevalence of mental health functioning (MHF) of student-athletes competing in the Canadian Interuniversity Sport (CIS) system at two different time points in their academic year (Fall = Time 1, Winter = Time 2) and (b) whether significant differences existed in their levels of MHF (emotional, social, and psychological well-being) between Time 1 and Time 2 and based on gender, alcohol use, living situation, year of study, and type of sport. Results indicated that the student-athletes from 30 different Canadian universities experienced moderate to high levels of MHF at both time points, including those who reported a previous mental illness diagnosis. Furthermore, there was a higher prevalence of flourishing compared to languishing student-athletes at both time points. Repeated measures MANOVA tests indicated that student-athletes’ MHF did not significantly differ across time based on their gender, alcohol use, living situation, year of study, and/or type of sport. However, when a 5-way MANOVA test was conducted with the larger sample Time 1 data to have more statistical power, results revealed a significant main effect of gender, suggesting that women had significantly lower levels of social well-being than men during the first part of the academic/athletic year (see Article 1). The second objective was to examine relationships between variables that could potentially influence the MHF of CIS student-athletes, namely, their stress, mood, self-regulation capacity, and perceptions of the coaching climate. A path analysis revealed that the student-athletes’ MHF was significantly impacted by the frequency of their maladaptive reactions to stressors, mood states, capability to self-regulate, and the climate fostered by coaches. The third aim was to determine if changes in student-athletes’ self-regulation capacity over the academic/athletic year were related to changes in the other variables of interest. A t-test was first run to establish whether there was a change in their self-regulation capacity from Time 1 to Time 2, however, their levels remained steady over these time points. A subsequent path analysis showed that change scores in self-regulation capacity were not significantly related to change scores in MHF, stress, mood, and perceptions of coaching climate (see Article 2). The hope is that the results of this study may inform the strategic directions of mental health promotion and maintenance programming designed for CIS student-athletes in the future.
Keywords: student-athletes; mental health; well-being; stress; mood; self-regulation; coaching climate; university sport